2007
DOI: 10.2466/pr0.100.1.171-176
|View full text |Cite
|
Sign up to set email alerts
|

Improved Advising Ratings in an Undergraduate Psychology Program

Abstract: During the late 1990s, the psychology department of Indiana University-Purdue University Indianapolis made investments in its undergraduate advising program in terms of additional professional personnel, a new orientation course, an experimental intrusive advising track, innovative peer activities, and expanded physical facilities. Against this backdrop of innovations, from 1995 to 2001 an exit survey of graduating seniors (N=311) showed improved evaluations of departmental counseling services. Ratings of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In two separate studies, Abelman and Molina (2000) and Jones (2013) found benefits to increasing intru siveness levels within an advising program. Rajecki and Lauer (2007) found that an exploratory intrusive advising program at Indiana University-Purdue University Indianapolis correlated with an increase in student satisfaction with course and career advising. Jeschke, Johnson, and Williams (2001) found that students who participated in intrusive advising reported higher levels of satis faction and feeling connected to the department, but the study participants were not more academ ically successful than students who received prescriptive advising.…”
mentioning
confidence: 96%
“…In two separate studies, Abelman and Molina (2000) and Jones (2013) found benefits to increasing intru siveness levels within an advising program. Rajecki and Lauer (2007) found that an exploratory intrusive advising program at Indiana University-Purdue University Indianapolis correlated with an increase in student satisfaction with course and career advising. Jeschke, Johnson, and Williams (2001) found that students who participated in intrusive advising reported higher levels of satis faction and feeling connected to the department, but the study participants were not more academ ically successful than students who received prescriptive advising.…”
mentioning
confidence: 96%
“…Despite the prevalence of preprofessional advising and the potentially important role it can play on college campuses, little research has been devoted to this topic. Studies have focused on the experiences of ''unsuccessful medical school applicants'' (Corder, 1982), advising in graduate programs (see, e.g., Knox, Schlosser, Pruitt, & Hill, 2006;Schlosser, Lyons, Talleyrand, Kim, & Johnson, 2011), or discipline-specific undergraduate advising (see, e.g., Karr-Lilienthal, Lazarowicz, McGill, & Menke, 2013;Rajecki & Lauer, 2007;Woolston, 2002). However, more study is needed to better understand preprofessional advising on college campuses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, these issues have been compounded by a prescriptive "feminization" of advising in which particular gendered assumptions about who should be advisors, and how advisors should and should not support students affect not only the nature of advising and the advising relationship, but they affect the identity of the advisor as well (Rajecki & Lauer, 2007). That is because the complex and multiple resources, identities, and standpoints that an advisor might leverage are violated when social scripts and policies constraining the nature and roles of advisors are present and enforced.…”
Section: List Ofmentioning
confidence: 99%
“…Culturally competent advisors help bridge these experiences of disenfranchisement to suggest ways to achieve positive outcomes (Rajecki & Lauer, 2007). Advisors must concentrate on effective advising spaces that transcend stereotypes perpetuated on diverse student populations through deliberate choice and efforts.…”
Section: Culturally Competent Advisingmentioning
confidence: 99%
See 1 more Smart Citation